2019
DOI: 10.3390/microorganisms7120706
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Microorganisms-Based Commercial Product on the Morphological, Biochemical and Yield of Tomato Plants under Two Different Water Regimes

Abstract: The practice of organic agriculture represents an essential requirement for conserving natural resources and for providing the food necessary for a growing population, on a sustainable basis. Tomatoes are considered to be one of the most important crops worldwide. In this context, the organic production of tomatoes should be taken into more consideration. The use of microorganisms-based commercial products is an alternative to chemical fertilizers. Anyway, the results of their use are still variable because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…It was also observed that at 472 nm wavelength, the lycopene values for most of the interactions were greater, though with no statistical significance as compared to those obtained at 502 nm. Similar values of the lycopene content were obtained by Inculet et al [ 29 ], and amounts below 6.82 mg·100 g −1 f.w. were recorded by Jędrszczyk and Ambroszczyk [ 30 ] with the organically fertilized tomato cultivar Mieszko F 1 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It was also observed that at 472 nm wavelength, the lycopene values for most of the interactions were greater, though with no statistical significance as compared to those obtained at 502 nm. Similar values of the lycopene content were obtained by Inculet et al [ 29 ], and amounts below 6.82 mg·100 g −1 f.w. were recorded by Jędrszczyk and Ambroszczyk [ 30 ] with the organically fertilized tomato cultivar Mieszko F 1 .…”
Section: Resultssupporting
confidence: 89%
“…However, the results regarding the interactions between cultivar, fertilization type, and irrigation regime showed significant differences only for the IB cultivar that was chemically fertilized with a 100% evapotranspiration replenishment or organically fertilized with a 67% evapotranspiration replenishment as compared to the cultivar HTP that was chemically fertilized and watered according to 67% replenishment. Similar values of the antioxidant activity were obtained in previous studies on tomato [ 6 , 29 ] and in related species such as red pepper [ 35 ]. Regarding fertilization type, organic fertilization gave a significantly higher antioxidant activity compared to chemical fertilization ( Table 3 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This circumstance, therefore, displays the need for sustainable use of agropharmaceuticals, together with the demand for more environment-friendly production systems: These topics in recent years have fuelled a growing public interest in the search for alternative approaches to chemical control in plant disease management [18]. In this context, microbial biocontrol is a biological strategy receiving increasing interest because of the environment-friendly nature of the solution, useful to design sustainable innovation [19,20]. Microbial-based biotools can find application both to control plant diseases and to reduce contaminations on the product [21].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, an increase of the antioxidant activity was also recorded (WMD: +0.94; 95% CI: +0.19, +1.70; I 2 = 74%; P = 0.01). [152][153][154][155][156][157][158][159][160], and plotted according to the mean difference. The weight of each study is represented by the size of the green box.…”
Section: Influence Of Pgpm Inoculum In Improving Nutritional and Nutraceutical Aspects On Fruitsmentioning
confidence: 99%